2012
DOI: 10.1098/rspb.2012.1745
|View full text |Cite
|
Sign up to set email alerts
|

The half-life of DNA in bone: measuring decay kinetics in 158 dated fossils

Abstract: Claims of extreme survival of DNA have emphasized the need for reliable models of DNA degradation through time. By analysing mitochondrial DNA (mtDNA) from 158 radiocarbon-dated bones of the extinct New Zealand moa, we confirm empirically a long-hypothesized exponential decay relationship. The average DNA half-life within this geographically constrained fossil assemblage was estimated to be 521 years for a 242 bp mtDNA sequence, corresponding to a per nucleotide fragmentation rate (k) of 5.50 Â 10 -6 per year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
446
6
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 493 publications
(490 citation statements)
references
References 65 publications
19
446
6
10
Order By: Relevance
“…Figure 3d shows no correlation, either for direct or relative dates. For non-UDGtreated libraries, Sawyer et al [41] and Allentoft et al [42] explored a wider range of dates and found a correlation.…”
Section: Results (A) Library Constructionmentioning
confidence: 99%
“…Figure 3d shows no correlation, either for direct or relative dates. For non-UDGtreated libraries, Sawyer et al [41] and Allentoft et al [42] explored a wider range of dates and found a correlation.…”
Section: Results (A) Library Constructionmentioning
confidence: 99%
“…feathers, bones, mummified remains, egg shells) are attributed to them [18][19][20]. Because of the availability of exceptionally preserved specimens, DNA recovered from various moa specimens has been used to differentiate species [20,21] and estimate rates of DNA degradation [22]. However, few complementary studies of moa proteins have been attempted [3,23].…”
Section: Introductionmentioning
confidence: 99%
“…Depurination affects the stability of the DNA backbone and leads to nicks and single-strand overhangs of the DNA fragments (2). Consequently, most free DNA fragments in the environment are <100 bp in size (3)(4)(5)(6)(7)(8). Deamination particularly affects cytosine, creating uracil residues that can lead to cytosine-tothymine exchanges, which result in DNA sequencing errors (9).…”
mentioning
confidence: 99%